Chapter 6: Gnullak koorliny University katitjin – Work with tertiary students - Buchanan, J.; Collard, Len; Cumming, Ingrid; Palmer, D.; Scott, Kim; Hartley, John (Cultural Science, 2016)
Another strategy adopted by the Noongapedia team was to experiment with combining Noongarpedia-posting with the learning activities in three university environments. The first of the groups involved in the Noongarpedia work was one that came to be called the ‘Noongarpedia hotshots’. These students were all Indigenous young people enrolled in a range of degree programs, based in the School of Indigenous Studies at the University of Western Australia. The second group were undergraduate students in a first-year course (Introduction to Community Development) designed for those keen on working with an approach noted for its commitment to ‘bottom-up’ and community driven involvement in social programs and solutions. These students were non-Indigenous young people. The third group were postgraduate students in the Masters of Heritage Studies undertaking a course on Debates in Contemporary Heritage Studies. These students included both Indigenous and non-Indigenous people.